2021
DOI: 10.1149/1945-7111/abe9cd
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Anodic Stripping Voltammetric Determination of Atropine in Urine Sample

Abstract: Overdose of atropine usually leads to heart failure and death and has long been used as a method of murder. We propose a simple electrochemical approach for atropine sensing using an electrode modified with nafion/polycarboxylate functionalized graphene nanoflakes (Nf/p-GNF/E). The polycarboxylate functionalized graphene nanoflakes were characterized by SEM, FT-IR, and electrochemical techniques. The electrochemical behavior and determination of atropine at the Nf/p-GNF/E were examined using cyclic voltammetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The p-GNF spectrum (Figure 1F(a)) presents an OH stretching band at 3423 cm −1 , symmetric and asymmetric CH 2 stretching vibrations at 2910 and 2868 cm −1 , respectively, a carbonyl group (CO) stretching band at 1741 cm −1 , and a carboxylate group (COO − ) stretching band at 1394 cm −1 . 5,54 This confirmed that the oxygen-containing functional groups from polycarboxylate were present on the surface of the GNFs, which can bond and induce Pd 2+ ions via coordinate covalent bonding. The spectrum of PdNC−GNF (Figure 1F(b)) shows clearly that the OH stretching band and the carbonyl group (CO) stretching band are significantly reduced and slightly shifted and that the carboxyl group (COOH) stretching band is no longer present.…”
Section: ■ Experimental Sectionmentioning
confidence: 56%
See 2 more Smart Citations
“…The p-GNF spectrum (Figure 1F(a)) presents an OH stretching band at 3423 cm −1 , symmetric and asymmetric CH 2 stretching vibrations at 2910 and 2868 cm −1 , respectively, a carbonyl group (CO) stretching band at 1741 cm −1 , and a carboxylate group (COO − ) stretching band at 1394 cm −1 . 5,54 This confirmed that the oxygen-containing functional groups from polycarboxylate were present on the surface of the GNFs, which can bond and induce Pd 2+ ions via coordinate covalent bonding. The spectrum of PdNC−GNF (Figure 1F(b)) shows clearly that the OH stretching band and the carbonyl group (CO) stretching band are significantly reduced and slightly shifted and that the carboxyl group (COOH) stretching band is no longer present.…”
Section: ■ Experimental Sectionmentioning
confidence: 56%
“…Formaldehyde (FA) is a carcinogenic substance widely and illegally used in many Asian countries to maintain the freshness and prolong the storage time of foodstuffs. It has been found in small amounts in raw foods such as fish, meat, milk, fruits, mushrooms, and vegetables. FA has been linked to severe neurological, respiratory, and digestive issues, and the International Agency for Research on Cancer (IARC) has determined the safe daily intake of FA to be 0.2 mg kg –1 body weight . Given the dangers of FA, it is critical to develop an accurate, rapid, and reliable method of detecting it in food samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A standard stock solution of atropine (1.0 × 10 −2 mol L −1 ) was prepared in deionized water and different working samples were prepared by serial dilution. Low-cost equipment, on the other hand, is utilized to test atropine including spectrophotometry [59], luminescence [60], electrochemiluminescence sensors [61], biosensor [62], voltammetry [63], and potentiometry [64]. These approaches, on the other hand, necessitate more time-consuming manipulation and costly chemicals.…”
Section: Reagents and Materialsmentioning
confidence: 99%
“…The development of electrochemical sensors has been promoted by the extensive use of carbonaceous nanostructured materials [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Graphene is known for its high surface area, rapid electron mobility, excellent conductivity, and mechanical stability [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%